Contemporary Management of Benign and Malignant Scrotal Conditions: Ablative and Reconstructive Challenges - Matthias D. Hofer; Gregory A. Dumanian; João Felício; Francisco E. Martins (Highlights on Medicine and Medical Research Vol. 9, 2021)
After surgical excision of both malignant and benign lesions, scrotal reconstruction is required.Given the unique anatomy of the scrotum some of the usual reconstructive techniques do not apply or at least not in general. The scrotum’s rugated and elastic skin tends to compensate for tissue loss, allowing regeneration even after 60% of the skin has been lost. On the downside, the exposed position of the scrotum and its mobility as well as the need to cover the testes pose a certain barrier to using skin grafts limiting the choices of tissues that can be used for reconstruction. We will review the most common malignant and benign diseases that surgeons will experience in this article, as well as identify a number of reconstructive techniques that will cover the majority of clinical scenarios.